2019
DOI: 10.1186/s12284-019-0317-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating rice for salinity using pot-culture provides a systematic tolerance assessment at the seedling stage

Abstract: Background Rice ( Oryza sativa L .) is one of the major staple food crops consumed globally. However, rice production is severely affected by high salinity levels, particularly at the seedling stage. A good solution would be the development of an efficient screening methodology to identify genotypes possessing genes for salt tolerance. Result A new salinity tolerance screening technique using rice seedlings in pot-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 35 publications
4
87
0
Order By: Relevance
“…Screening and breeding salinity‐tolerant cultivars is crucial for rice production in saline‐alkaline soils. Generally, in rice plants growing in saline‐alkaline soils, several physiological processes such as photosynthesis, respiration, and hormonal regulation are negatively affected, and this results in unbalanced nutrient absorption and reduced crop yields (Kakar, Jumaa, Redoña, Warburton, & Reddy, 2019; Negrão, Schmöckel, & Tester, 2017). Currently, the lack of high‐yielding, salt‐tolerant rice varieties and crop management practices customized for saline‐alkaline soils is a major barrier to rice production.…”
Section: Introductionmentioning
confidence: 99%
“…Screening and breeding salinity‐tolerant cultivars is crucial for rice production in saline‐alkaline soils. Generally, in rice plants growing in saline‐alkaline soils, several physiological processes such as photosynthesis, respiration, and hormonal regulation are negatively affected, and this results in unbalanced nutrient absorption and reduced crop yields (Kakar, Jumaa, Redoña, Warburton, & Reddy, 2019; Negrão, Schmöckel, & Tester, 2017). Currently, the lack of high‐yielding, salt‐tolerant rice varieties and crop management practices customized for saline‐alkaline soils is a major barrier to rice production.…”
Section: Introductionmentioning
confidence: 99%
“…in the field (Kakar et al, 2019). Furthermore, it may not be sufficient to use shoot and root growth parameters only for the classification of breeding lines as tolerant and sensitive.…”
Section: Crop Sciencementioning
confidence: 99%
“…It is also helpful to provide an additional benefit towards understanding the underlying physiology and genetic mechanisms of tolerance at sensitive stages of plant growth (Ismail and Horie 2017). The correct phenotypic evaluation of genotypes is significant for salinity tolerance based on genetic approaches (Kakar et al 2019). Different morpho-physiological indexes are responsible for the tolerance to salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Different morpho-physiological indexes are responsible for the tolerance to salt stress. Kakar et al (2019) used distinct morpho-physiological traits, such as plant height, tiller number, leaf area, root length, root surface area, chlorophyll contents, flavonoids, and nitrogen balance index, to evaluate the salt tolerance of rice at the seedling stage. They concluded that root parameters might be more reliable than other parameters.…”
Section: Introductionmentioning
confidence: 99%